2015
DOI: 10.15760/trec.123
|View full text |Cite
|
Sign up to set email alerts
|

Seismic Retrofit Benefit Considering Statewide Transportation Assessment

Abstract: Type of Report and Period CoveredFinal Report 14. Sponsoring Agency Code 15. Supplementary Notes 16. Abstract -The purpose of this study was to identify and demonstrate a methodology to prioritize bridges for retrofit in the State of Oregon. Given the limited resources available, retrofitting all vulnerable bridges in the foreseeable future would not be practical. Instead, a retrofit strategy needs to be developed to prioritize the inventory and enumerate the retrofit cost. In this study, a prioritization meth… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2015
2015
2024
2024

Publication Types

Select...
2
1
1

Relationship

1
3

Authors

Journals

citations
Cited by 4 publications
(1 citation statement)
references
References 25 publications
0
1
0
Order By: Relevance
“…Fragility development methods can be categorized in empirical methods, experimental methods, expert opinions, and analytical methods. A detailed literature review of fragility curves development methods can be found in Mehary and Dusicka (Mehary and Dusicka 2015), and in Muntasir Billah and Alam (Muntasir Billah and Alam 2014).…”
Section: Fragility Development Methodsmentioning
confidence: 99%
“…Fragility development methods can be categorized in empirical methods, experimental methods, expert opinions, and analytical methods. A detailed literature review of fragility curves development methods can be found in Mehary and Dusicka (Mehary and Dusicka 2015), and in Muntasir Billah and Alam (Muntasir Billah and Alam 2014).…”
Section: Fragility Development Methodsmentioning
confidence: 99%